Stability of Ceftiofur Sodium and Cefquinome Sulphate in Intravenous Solutions - Agnieszka Dołhań; Anna Jelińska; Marcelina Bębenek (The Scientific World Journal)
Stability of ceftiofur sodium and cefquinome sulphate in intravenous solutions was studied. Chromatographic separation and quantitative determination were performed by using a high-performance liquid chromatography with UV-DAD detection. During the stability study, poly(vinylchloride) minibags were filled with a solution containing 5 mg of ceftiofur sodium or cefquinome sulphate and diluted to 0.2 mg/mL with suitable intravenous solution depending on the test conditions. The solutions for the study were protected from light and stored at room temperature (22°C), refrigerated (6°C), frozen (−20°C) for 30 days, and then thawed at room temperature. A comparison of results obtained at 22°C and 6°C for the same intravenous solutions showed that temperature as well as components of solutions and their concentration had an influence on the stability of ceftiofur sodium and cefquinome sulphate. It was found that ceftiofur sodium and cefquinome sulphate dissolved in intravenous solutions used in this study may be stored at room temperature and at 6°C for up to 48 h.